Dimens\~oes do acesso a medicamentos no Brasil: Perfil e desigualdades dos gastos das famílias, segundo as pesquisas de orçamentos familiares 2002-2003 e 2008-2009 - Leila Posenato Garcia; Luís Carlos Garcia de Magalh\~aes; Ana Cláudia Sant'Anna; Lúcia Rolim Santana de Freitas; Adriana Pacheco Aurea (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Access to medicines in Brazil can be studied using different analytical approaches. One of these approaches is the household spending on medicines, whose weight over the income of the Brazilian families is widely known. The study aims to describe the spending on medicines of the Brazilian families and to analyse socioeconomic inequalities in these expenditures. The study innovates, in relation to previous studies by describing the expenditures according to categories of medicines and on providing an analysis of the spending inequalities that incorporates, not only the aspect of income, but also the self-perception of living conditions of these families. The microdata used are from the Family Budget Surveys (POF) conducted in 2002-2003 and 2008-2009 by the Brazilian Institute of Geography and Statistics (IBGE). The spending on medicines, one of the main components of the health expenditures of Brazilian families, had a positive change of 10% in its absolute value, during the period studied. According to POF 2008-2009, the average expenditure was R 59.02. About 77% of the families recorded an average spending of R 76.31 on medicines during the reference period for data collection. The average of per capita expenditure on medicines was R 17.91. Families belonging to the bottom income decile had spent R 4.47, while those belonging to the top decile had spent R 58.44. Families with lower incomes undertook proportionately greater fraction of their income on purchasing medicines than those with higher incomes. In 2008-2009, the families in the top decile of income spent on medicines, in absolute terms, thirteen times the amount spent by those belonging to the bottom decile, despite the fact that families with lower income spend much less than those with higher incomes on acquiring these essential goods. The study showed an increase in the proportion of families that had expenditure of certain categories of medicines, especially analgesics, cold medication, and medicines for cholesterol and heart diseases. In turn, there was a reduction in the proportion of families that had expenditures on anti-infective and anti-inflammatory agents. The high inequality in income distribution still prevalent in the Brazilian society has been manifested, in the same way, in the high inequality of household spending on medicines.
Keywords: I18; 330; health economics; national drug policy; pharmaceutical preparations; health inequalities; financing; personal; health expenditures; family